2003
DOI: 10.1002/j.1556-6678.2003.tb00244.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culture on Group Behavior: A Comparison of Three Ethnic Groups

Abstract: The purpose of this study was to compare behavior in group counseling of Moslem, Druze, and Jewish adolescents in Israel. On the basis of the literature, differences were expected between the three groups on all dimensions under investigation: self-disclosure, affiliation (response to self-disclosure), and gains. The Jewish adolescents were expected to show the highest rates of selfdisclosure, affiliation, and gains; Moslems were expected to be next; and the Druze were expected to have the lowest rates. Contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
(23 reference statements)
3
13
2
Order By: Relevance
“…This was based on self-disclosure models (Joinson, 2001a;Joinson & Paine, 2007;Omarzu, 2000) and an adaptation of the Rating Scale for Self-disclosure (Vondracek & Vondracek, 1971), which measures selfdisclosure among adolescents. The inter-rater agreement in studies that used this tool (Shechtman, Hiradin, & Zina, 2003) found it to be reliable (kappa coefficient 0.95-0.99). The tool was further adapted and used to measure online self disclosure among an adult population in Israel.…”
Section: Methodsmentioning
confidence: 99%
“…This was based on self-disclosure models (Joinson, 2001a;Joinson & Paine, 2007;Omarzu, 2000) and an adaptation of the Rating Scale for Self-disclosure (Vondracek & Vondracek, 1971), which measures selfdisclosure among adolescents. The inter-rater agreement in studies that used this tool (Shechtman, Hiradin, & Zina, 2003) found it to be reliable (kappa coefficient 0.95-0.99). The tool was further adapted and used to measure online self disclosure among an adult population in Israel.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the Muslims and Christians who live in Israel are considered bicultural. The Druze, in contrast, are distinguished from the other two in terms of their religion, geography, ethnicity, and political stands (Danah, 2000), and they are very strict in their socialization of the young generation (Shechtman, Hiradin, & Zina, 2003).…”
Section: Differentiation In Eastern Culturesmentioning
confidence: 98%
“…In our own study, the descriptions of parent relationships among our interviewees often equated their experience of the parent-child relationship to a friendship or sibling relationship. On the surface, these descriptions seem to be inconsistent with the authoritarian role of parents typically attributed to traditional Arab families (Azaiza, 2005; Mikulincer et al, 1993; Shechtman et al, 2003). Future research is needed to determine whether these sentiments are shared by the parents or simply seen through the eyes of their children.…”
Section: Discussionmentioning
confidence: 94%
“…The interview questions were based on an understanding of qualitative inquiry (Edwards & Holland, 2013; Mason, 2002) and research on traditional families (Azaiza, 2005; Lavee & Katz, 2002; Mikulincer, Weller, & Florian, 1993; Shechtman, Hiradin, & Zina, 2003). The development of the interview questions and subsequent analyses also benefited from the unique composition of the research team.…”
Section: Methodsmentioning
confidence: 99%